Data resource profile: children looked after administrative records in Wales - Allnatt, Gemma; Lee, Alexandra; Scourfield, Jonathan; Elliott, Martin; Broadhurst, Karen; Griffiths, Lucy (International Journal of Population Data Science, 2022)
Introduction Children who are 'looked after' by the State are considered one of the most vulnerable groups in society. Being in State care is associated with poor social, educational and health outcomes. Exploring how to improve the system and better support children in care is key to improving these outcomes. When children and young people come to the attention of children's social services a significant amount of information about their care experience is routinely collected by local authorities. In Wales, routine data are captured in the 'Children Looked After' Census which is submitted annually to the Welsh Government and has recently been shared with the Secure Anonymised Information Linkage (SAIL) Databank. Method The aim of this paper is to provide an overview of the main 'Children Looked After' Census dataset and its subsets. These datasets contain rich, situational and individual level data on children looked after, such as information on placement types, education and leaving care. We outline the strengths and limitations of the available information and how to access the data. Results The 'Children Looked After' Census has recently been made available for research purposes and access to it will enable researchers to explore and understand at population level the journey through the care system and outcomes of leaving care. There is also the opportunity, through the SAIL Databank, for data linkage to health, education and family justice datasets, allowing research to holistically explore other factors associated with being in care. Conclusion These data provide a rich source of information about children and young people who have been in care in Wales. They offer researchers opportunities to better understand the care system and outcomes for this within it. Findings will have important implications for making improvements in children's social care policy and practice.